PEMANFAATAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN LURING DI UPT SD NEGERI 295 GRESIK - Mar’atul Hasanatin; Ika Ratih Sulistiani; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
This study aims to describe the implementation of the use of audio visual media in offline learning at UPT SD Negeri 295 Gresik and describe audio visual media to increase the effectiveness of offline learning at UPT SD Negeri 295 Gresik. Sources of data were obtained from fourth grade teachers and school principals. This study uses qualitative methods with two objects, namely primary and secondary, field observations, interview and documentation to obtain findings based on the research focus to be answered. Laoptops and loundspeakers, to increase the effectiveness of learning, quality video material is needed so that it can make students easy to understand.